The Application of Technology to Human Resources in The Civil Servant Recruitment Selection Process - Hasanah, Rika; Jauhari, Tontowi (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2024)
This study explains the application of technology in human resource management, specifically in the process of Civil Servant Candidate (CPNS) recruitment and selection. The aim of the research is to analyze how technology can enhance efficiency, transparency, and objectivity in this process. The method used is descriptive qualitative research with a literature review approach. Through this method, relevant journals and literature are systematically reviewed to gain in-depth understanding. The findings indicate that technologies, such as the use of Computer Assisted Test (CAT) and e-Meterai, play a crucial role in supporting better human resource management. These technologies not only reduce paper usage (paperless) but also improve document validity, accelerate administrative processes, and enable more accurate decision-making.